2021
DOI: 10.1038/s41598-021-97469-z
|View full text |Cite
|
Sign up to set email alerts
|

Higher ultraviolet radiation during early life is associated with lower risk of childhood type 1 diabetes among boys

Abstract: Population-level ecological studies show type 1 diabetes incidence is inversely correlated with ambient ultraviolet radiation (UVR) levels. We conducted a nested case–control study using administrative datasets to test this association at the individual level. Cases (n = 1819) were children born in Western Australia (WA) from 1980–2014, diagnosed with type 1 diabetes at ≤ 16 years. Controls (n = 27,259) were randomly selected from all live births in WA, matched to cases by sex and date of birth. Total ambient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 48 publications
(59 reference statements)
0
3
0
Order By: Relevance
“…There is also recent evidence that exposure to higher intensity of UV radiation during early life may protect from the development of type 1 diabetes—an autoimmune disease of the pancreas. In a data-linkage-based cohort study of 29,078 children in Western Australia (~ 6% of whom were diagnosed with type 1 diabetes by age 16), higher ambient (erythemally weighted) UV radiation was associated with reduced risk of developing type 1 diabetes, but only in males and only for UV radiation during the 3rd trimester and 1st year of life [ 248 ]. The authors concluded, assuming a causal association, that for every 100 kJ m −2 increase in total lifetime dose of ambient UV radiation dose, the relative risk of developing type 1 diabetes in males decreased by 29%.…”
Section: Benefits Of Exposure To Uv Radiationmentioning
confidence: 99%
“…There is also recent evidence that exposure to higher intensity of UV radiation during early life may protect from the development of type 1 diabetes—an autoimmune disease of the pancreas. In a data-linkage-based cohort study of 29,078 children in Western Australia (~ 6% of whom were diagnosed with type 1 diabetes by age 16), higher ambient (erythemally weighted) UV radiation was associated with reduced risk of developing type 1 diabetes, but only in males and only for UV radiation during the 3rd trimester and 1st year of life [ 248 ]. The authors concluded, assuming a causal association, that for every 100 kJ m −2 increase in total lifetime dose of ambient UV radiation dose, the relative risk of developing type 1 diabetes in males decreased by 29%.…”
Section: Benefits Of Exposure To Uv Radiationmentioning
confidence: 99%
“…In addition, other putative environmental modifiers of disease risk, coupled with genetic susceptibility, are proposed to increase the likelihood of developing T1D. For example, viral exposure, 6 lack of sunlight, 7,8 hygiene 9 and diet 10 have all been considered disease‐modifying risk factors.…”
Section: Introductionmentioning
confidence: 99%
“…Through its effects on circadian rhythms, sunlight can influence the neuroendocrine system, cognitive function, and mood ( 4 ). Moreover, a large number of epidemiological studies have substantiated the correlation between sunlight exposure levels and a diminished risk of all-cause mortality ( 5 ), as well as various related diseases such as myopia ( 6 ), asthma ( 7 ), type 1 diabetes ( 8 ), autism ( 9 ), colorectal cancer ( 10 ), and Alzheimer’s disease ( 11 ). Additionally, a potential mechanism underlying the connection between sunlight and public health is the conversion of 7-dehydrocholesterol in the human skin into vitamin D. This process is essential for the vitamin D synthesis of the body ( 12 , 13 ), a deficiency of which can contribute to osteoporosis ( 14 ), multiple sclerosis ( 15 ), diabetes mellitus ( 16 , 17 ), cardiovascular diseases ( 18 ), sleep disorders ( 19 , 20 ), obesity ( 21 ), depression ( 22 ), and anxiety and cognitive impairment ( 23 , 24 ).…”
Section: Introductionmentioning
confidence: 99%